The weather disaster - McElligott, Matthew (McElligott, Matthew. Mad Scientist Academy, 2016)
"In the second book of the series, Dr. Cosmic's class of clever monsters must face down blizzards, thunderstorms, floods, and tornadoes, in this perfect blend of adventure and exploration"--